Academic achievement and aggressive behavior in college students (European Journal of Child Development, Education and Psychopathology, 2014)
Academic achievement in higher education is analyzed in most cases, from a perspective that puts special emphasis on factors related to motivation or quality of teaching practices. However, the presence of violent behavior in secondary education, makes rethink the need to address this issue also in the university context. The aim of this paper is to analyze the academic performance and the presence of aggressive behaviors in college students, attending to gender and qualification (Degree in Early Childhood Education, Degree in Elementary Education and Degree in Psychology). To do this, he had a sample of 219 university students, with a mean age of 19.79 years. The instruments used were the School Aptitude Test (TEA-Level 3) and Questionnaire Reactive-Proactive Aggression (RPQ). The results of the MANOVA showed significant main effects of qualifications and between the sexes, although no effects were observed in their interaction (title-sex). As for aggressive behavior significant main effects between the sexes were given, but not between the degrees or the degree-sex interaction.